Spatial distribution of the impact of surface mining on the landscape ecological health of semi-arid grasslands. (April 2020) - Wu, Zhenhua; Lei, Shaogang; Lu, Qingqing; Bian, Zhengfu; Ge, Sijie
Highlights: Propose a Modified Landscape Disturbance Index. Determine the spatial distribution of surface mining impact on grasslands. The impact of surface mining on grasslands landscape ecology is heterogeneous. Abstract: Coal mining and utilization have always been a great impact on landscape ecology. Many studies have identified the impact of surface mining through landscape changes, but the spatial distribution and extent of the impacts are considered less in existing studies. The objective of this study is to determine the spatial distribution and extent of the impact of surface mining on the Landscape Ecological Health (LEH) of semi-arid grasslands. The research area of this paper is Shengli surface mines, Xilinhot City, Inner Mongolia Autonomous Region, China. The main steps of the research method include LEH assessment, buffer analysis, Landscape Ecological Function Contribution Rate (LEFCR) and Modified Landscape Disturbance Index (MLDI) measurement. The results indicated that: 1) the theoretical reference range of the impact of Shengli surface mines on the semi-arid grassland LEH is 5 km. 2) The proposed MLDI can effectively monitor the disturbance of surface mining on landscape ecology. 3) The heavily affected area is mainly the open-pit landscape; the moderately affected area is mainly the dumping landscape and the mining area industrial square landscape, and the slightly affected area is mainly a small part of the dumping landscape and the surrounding grassland landscape of the mining area. The spatial distribution of the impact of surface mining on the landscape ecology of semi-arid grasslands is heterogeneous, which should be taken into account in landscape ecological management, restoration, and planning. This paper may serve as a reference for the study of the disturbances and impacts of human activities on landscape ecology.